Estudo comparativo entre edições da sonata OP.94 para flauta e piano de Sergei Prokofiev: subsídios para a escolha da edição e interpretação da peça - Maira Urbano Neto (2007)
Sergei Prokofiev's Sonata OP. 94, originally written for flute and piano, has been transcribed by the composer for violin and piano, soon after its premiere. The transcription had a strong influence over the subsequent editions of flute sonata. This article presents a comparative analysis of several editions of Sonata ( both for flute and piano and for violin and piano) in order to demonstrate and describe the differences and similarities between editions, as well as offer resources for well-infored choices regarding the edition and interpretations of this piece - a work of such relevance for the of twentieth century's transverse flute repertoire.